Common Grace And Hermeneutics: Utilizing Abraham Kuyper’s Common Grace For Facing Changes In Hermeneutics - Surya Harefa (STTRII, 2021)
This article tries to further the suggestion of utilizing the concept of common grace popularized by Abraham Kuyper (1837-1920) for facing changes in hermeneutics. Hermeneutics has changed in many ways because of the influences of modernism and postmodernism. In contrast to more liberal theologians who promote those changes actively, evangelical theologians tend to response negatively or hesitantly. After describing briefly those hermeneutical changes, this article investigates Kuyper’s doctrine of common grace. As conclusion, it provides some suggestions on to what extent the concept of common grace can be utilized for reconsidering changes in hermeneutics as favourable opportunities to develop more the field of hermeneutics.